Pratiquer une réflexion épistémologique sur les sciences dans une école communautaire du Québec : exemple de tension entre savoirs diffusés et savoirs locaux. - Hervé Ferrière; Laurence Ferrière (Éducation et Socialisation)
We think generally, in most of the western countries, that the pupils and the teachers know difficulties during the teaching of the experimental sciences. Multiple causes, often vague, are advanced to explain them. To propose concrete methods of learning, we tried to test, in a particular context, a particular reason : do not know, at first, the various forms of knowledges which exist (P. Hirst), then the relations between scientific knowledges and local knowledges (named cultural or traditional knowledges), and, finally, the story of the spreading of scientific knowledges. We led discussions with philosophic objectives around these questions with a small group of 14 or 15 years old pupils, within Native’s school of Quebec. There, We present our working hypotheses and results.